Leveraging Digital Technologies for Sustainable Agriculture in Enhancing Social and Economic Development in Kenya - Jumanne, Andrew (International Journal of Agriculture, 2024)
Purpose: This seminar paper explored the potential of digital technologies in driving sustainable agriculture and promoting social and economic development in Kenya. Drawing upon empirical research, the paper investigated the impact of digital innovations on agricultural practices and analysed the benefits and challenges associated with their adoption. Methodology: The study utilised a mixed-methods approach, involving qualitative and quantitative data collection and analysis methods. A stratified random sampling technique was employed to ensure a representative sample of farmers from various regions in Kenya, while purposive sampling was used to select key informants including policymakers, agricultural experts, and representatives from relevant institutions and corporations. The research targeted three main groups: farmers, key informants, and participants in focus group discussions (FGDs), with the estimated farmer population in Kenya being approximately 330,000, segmented by agro-ecological zones. Descriptive statistical analysis, frequencies, percentages, and measures of central tendency, summarised the quantitative data, while inferential statistical techniques, regression analysis, were applied to explore relationships between digital technology adoption, agricultural practices, and social and economic outcomes. Thematic analysis was conducted to extract key themes, patterns, and insights from qualitative data collected through interviews and focus group discussions. Findings: The study revealed that farmers in the age group of 36-55 years and 18-35 years exhibited the highest adoption rates, highlighting the inclination of younger and middle-aged farmers towards digital technologies. However, a gender disparity existed, with male farmers showing higher adoption rates compared to female farmers, suggesting the need for targeted interventions. Education level emerged as a significant factor influencing adoption, emphasizing the importance of digital literacy and access to information. Further, larger-scale farmers demonstrated a higher adoption rate, indicating the influence of resources and capacity in technology investment. Regional variations in adoption rates also existed, with the Highlands region exhibiting the highest adoption rate. Regression analysis confirmed the positive impact of technology adoption on agricultural practices and identified policy support and farmer training as key drivers. However, access to finance does not show a statistically significant relationship. Unique Contribution to Theory, Practice and Policy: Based on these findings, the paper puts forward recommendations to enhance the adoption and effective utilisation of digital technologies in agriculture. These include promoting digital literacy and awareness, implementing gender-inclusive strategies, improving access to financing, fostering policy support, strengthening farmer training and extension services, encouraging public-private partnerships, supporting research and innovation, and establishing robust monitoring and evaluation systems. By incorporating these recommendations, Kenya can create an enabling environment for the adoption of digital technologies in agriculture, leading to sustainable practices, enhanced social and economic development, and improved livelihoods. This paper contributes to the ongoing discourse on harnessing Africa's diversity and demographic dividends for Socio-Economic transformation for a more inclusive, resilient, and prosperous agricultural sector.